OPTIMASI PENGOLAHAN TEH KULIT BUAH NAGA (Hylocereus polyrhizus) - Mukhti Ali (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2016)
Dragon fruit skin that had not been processed as waste in an optimal, even just be a waste to society, but the skin can be processed into a dragon fruit dragon fruit peel tea. The purpose of this study was to determine the levels of antioxidants and antioxidant activity, as well as the preference level of the tea panelists red dragon fruit peel and white by using the oven drying method, UV plastic, and direct sunlight. The study also aimed to analyze variations in the type of dragon fruit and drying techniques to the levels of antioxidants and antioxidant activity, as well as the properties of tea organoliptik dragon fruit skin. In this study used six combinations between types of dragon fruit (Red and White) and the drying method (Oven, Plastic UV and Direct Sunlight. The parameters analyzed were the levels of antioxidants and antioxidant activity and the level of A panelist on color, flavor, and aroma.The results show that there is significant influence on the kind of dragon fruit antioxidant levels and antioxidant activity at the 5% significance level. While the drying method does not give a different effect on the levels of antioxidants and antioxidant activity. The next type of dragon fruit also gives different effect on the preference level of the color of tea panelists dragon fruit skin, while the drying method does not provide a real impact. However, the type of dragon fruit no significant effect on the taste and aroma of tea dragon fruit skin. As well as the drying method, no significant effect on the taste and aroma of tea dragon fruit skin.  Keywords: dragon fruit skin, drying, tea, antioxidant levels, antioxidant activity.